2018
DOI: 10.1128/iai.00361-18
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1 and Caspase-11 Mediate Pyroptosis, Inflammation, and Control of Brucella Joint Infection

Abstract: Brucellosis, caused by the intracellular bacterial pathogen is a zoonotic disease for which arthritis is the most common focal complication in humans. Here we investigated the role of inflammasomes and their effectors, including IL-1, IL-18 and pyroptosis, on inflammation and control of infection during-induced arthritis. Early in infection, both caspase-1 and caspase-11 were found to initiate joint inflammation and pro-inflammatory cytokine production. However, by one week post-infection caspase-1 and caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 62 publications
(92 reference statements)
4
67
0
Order By: Relevance
“…Recently, we reported that inflammasomes induce joint inflammation, but also contribute to control of infection during Brucella ‐induced arthritis . Inflammasomes are multiprotein structures that use sensors, such as NLRP3 and AIM2, to detect intracellular, cytosolic threats .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that inflammasomes induce joint inflammation, but also contribute to control of infection during Brucella ‐induced arthritis . Inflammasomes are multiprotein structures that use sensors, such as NLRP3 and AIM2, to detect intracellular, cytosolic threats .…”
Section: Introductionmentioning
confidence: 99%
“…induction and activation of caspase-11 in macrophages [25][26][27]. Although the mechanism of TRIF-induced activation of the caspase-11 non-canonical inflammasome is still unclear, TRIF in the TLR-TRIF axis is a critical molecule to activate caspase-11 non-canonical inflammasome during the inflammatory responses.…”
Section: Activatorsmentioning
confidence: 99%
“…TIR-domain-containing adapter-inducing interferon β (TRIF) is an intracellular TLR adaptor to transduce the inflammatory signal cascades from TLRs in the inflammatory cells [7]. TRIF was reported as an activator of the caspase-11 non-canonical inflammasome i.e., infection of cells with Gram-negative bacteria induced the TRIF signaling pathway in macrophages, leading to the induction and activation of caspase-11 in macrophages [25][26][27]. Although the mechanism of TRIF-induced activation of the caspase-11 non-canonical inflammasome is still unclear, TRIF in the TLR-TRIF axis is a critical molecule to activate caspase-11 non-canonical inflammasome during the inflammatory responses.…”
Section: Ligand Internalizationmentioning
confidence: 99%
“…In that case, caspase‐11 deficiency augmented bacterial burden in lungs, spleen, and liver . Similarly, caspase‐11 controlled Brucella melitensis joint infection and exacerbated joint inflammatory response against this pathogen . Moreover, recent data revealed that during B. abortus systemic infection, caspase‐11 −/− mice are more susceptible compared to wild‐type animals and they recruited fewer immune cells such as neutrophils, Mϕ s, and dendritic cells (DCs) in mouse spleens .…”
Section: Caspase 11: the Noncanonical Inflammasome Receptormentioning
confidence: 99%
“…34 Similarly, caspase-11 controlled Brucella melitensis joint infection and exacerbated joint inflammatory response against this pathogen. 35 Moreover, recent data revealed that during B. abortus systemic infection, caspase-11 −/− mice are more susceptible compared to wild-type animals and they recruited fewer immune cells such as neutrophils, M s, and dendritic cells (DCs) in mouse spleens. 36 Additionally, Gram-negative bacteria such as Burkholderia pseudomallei and B. thailandensis that naturally invade the cytosol are targeted by caspase-11.…”
Section: Caspase 11: the Noncanonical Inflammasome Receptormentioning
confidence: 99%